THE EFFECT OF EARLY MOBILIZATION ON REDUCING THE RISK THROMBOSIS INMOTHERS AFTER CESAREAN SURGERY - Parida, Wirna; Retno Wahyuni; Lilis Monica; Imarina; Yuli Kartika (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: A cesarean section (C-section) is a surgical procedure performed to deliver a baby through an incision in the mother’s abdomen and uterus. As the number of deliveries via this method increases, attention to the postoperative wound healing process has become increasingly crucial. In Indonesia, according to the 2023 Basic Health Research (Riskesdas), the rate of cesarean section (CS) deliveries has increased compared to previous years. This increase indicates the need for greater attention to aspects of postoperative care, including early mobilization. The objective of this study is to analyze the effect of early mobilization on reducing the risk of thrombosis in mothers following cesarean section at Citra Medika Tembung Hospital, Deli Serdang Regency, in 2025. Research Methodology: This study employed a qualitative-analytical approach with a cross-sectional design. The study population consisted of 32 participants. Data were collected through direct observation using an observation sheet and analyzed using the Chi-Square test at a 95% confidence level. The results indicate a significant association between early mobilization and a reduced risk of thrombosis (p-value < 0.05). Mothers who underwent early mobilization experienced faster wound healing and exhibited a reduction in clinical symptoms associated with thrombosis risk compared to those who did not undergo early mobilization. The conclusion of this study is that early mobilization has a significant effect on reducing the risk of thrombosis in mothers following cesarean section.